1999
DOI: 10.1044/jslhr.4205.1061
|View full text |Cite
|
Sign up to set email alerts
|

Brief-Tone Frequency Discrimination by Children

Abstract: This study investigated maturational changes in children's ability to discriminate the frequency of short-duration tone pulses. Frequency difference limens (DLs) were measured for digitally generated 1000-Hz tones with pulse durations of 200, 50, and 20 ms using a two-alternative, two-interval, forced-choice procedure. Participants were 16 5-year-old children; 10 children each in the age categories of 7, 9, and 11 years; and a control group of 10 young adults. Eleven of the 5-year-old children were unable to l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
61
3
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(79 citation statements)
references
References 42 publications
14
61
3
1
Order By: Relevance
“…The discrimination thresholds measured in this study are noticeably higher than some reported in previous investigations with children (Thompson, Cranford, & Hoyer, 1999). However, results are not directly comparable because of the effects of practice.…”
Section: Comparison With Existing Datacontrasting
confidence: 80%
“…The discrimination thresholds measured in this study are noticeably higher than some reported in previous investigations with children (Thompson, Cranford, & Hoyer, 1999). However, results are not directly comparable because of the effects of practice.…”
Section: Comparison With Existing Datacontrasting
confidence: 80%
“…Children's ability to discriminate frequency differences has also been extensively investigated (Maxon and Hochberg, 1982;Jensen and Neff, 1993;Cooper, 1994;Thompson et al, 1999). Overall the results suggest that young children have larger difference limens (DLs) than 8-yr-old (y.o.)…”
Section: A Pitch Perception In Childrenmentioning
confidence: 58%
“…Frequency discrimination of brief-duration tones (20 ms) reaches adult-like characteristics by the age of 7 years (Thompson et al, 1999) as does the ability to discriminate between spectrally overlapping sound sequences (Allen and Nelles, 1996). Therefore, if the segregation process was based solely upon the child's ability to discriminate between the frequencies of tones, then the 9-11-year-old group should have displayed similar results as adults.…”
Section: Discussionmentioning
confidence: 87%